2021
DOI: 10.1371/journal.pgen.1009127
|View full text |Cite
|
Sign up to set email alerts
|

Rad21l1 cohesin subunit is dispensable for spermatogenesis but not oogenesis in zebrafish

Abstract: During meiosis I, ring-shaped cohesin complexes play important roles in aiding the proper segregation of homologous chromosomes. RAD21L is a meiosis-specific vertebrate cohesin that is required for spermatogenesis in mice but is dispensable for oogenesis in young animals. The role of this cohesin in other vertebrate models has not been explored. Here, we tested if the zebrafish homolog Rad21l1 is required for meiotic chromosome dynamics during spermatogenesis and oogenesis. We found that Rad21l1 localizes to u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…Recent studies have identified key structures of zebrafish meiotic chromosomes and their functions in pairing and recombination (Feitsma et al, 2007;Kochakpour and Moens, 2008;Saito et al, 2014;Blokhina et al, 2019Blokhina et al, , 2021Takemoto et al, 2020;Zhang et al, 2020;Imai et al, 2021;Islam et al, 2021). These studies not only revealed conserved roles of such structures, but also provided new insights into how they contribute to meiotic recombination.…”
Section: Chromosome Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have identified key structures of zebrafish meiotic chromosomes and their functions in pairing and recombination (Feitsma et al, 2007;Kochakpour and Moens, 2008;Saito et al, 2014;Blokhina et al, 2019Blokhina et al, , 2021Takemoto et al, 2020;Zhang et al, 2020;Imai et al, 2021;Islam et al, 2021). These studies not only revealed conserved roles of such structures, but also provided new insights into how they contribute to meiotic recombination.…”
Section: Chromosome Structuresmentioning
confidence: 98%
“…Since zebrafish do not have sex chromosomes, there are no asynapsed regions that are typically associated with unpaired heteromorphic sex chromosomes as is seen in some fish species (Devlin and Nagahama, 2002;Wallace and Wallace, 2003). Occasionally, some asynapsis and separation of the axes is seen near telomeres, which can be easily observed using super-resolution microscopy, possibly indicating that the cells are transitioning to the diplotene stage (Blokhina et al, 2021). Up to the pachytene stage, staining and imaging of chromosomes using super-resolution microscopy or electron microscopy show spermatocytes and oocytes are nearly identical except that fully synapsed pachytene chromosomes are somewhat longer in females (Wallace and Wallace, 2003;Kochakpour and Moens, 2008;Blokhina et al, 2019).…”
Section: Pachytene Stagementioning
confidence: 99%
“…Meiosis-I resumes at the maturation stage, which occurs just prior to ovulation in zebrafish (stage IV), then arrests again in meiosis-II until fertilization takes place ( Selman et al, 1993 ). Multiple meiotic mutants have all or mostly male phenotypes in zebrafish, including mutants disrupting SC encoding genes sypc1 and sycp2 , as well as a cohesin complex encoding gene rad21l1 ( Takemoto et al, 2020 ; Blokhina et al, 2021 ; Imai et al, 2021 ). In mutants affecting SC components, oogenesis was initiated, as juvenile fish had ovarian follicles at 40 dpf ( sycp1 –/– ) and 28 dpf ( sycp2 –/– ) ( Takemoto et al, 2020 ; Imai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the sycp1 and sycp2 mutants, oogenesis did not proceed to stages that could support ovary development into adulthood. In rad21l1 mutants, which is the zebrafish ortholog of mouse Rad21l , nearly all fish developed as fertile adult males, suggesting a function in oogenesis but not spermatogenesis ( Blokhina et al, 2021 ). During development, most rad21l1 mutant fish initially had immature oocytes demonstrating that, similar to sycp1 and sycp2 mutants, oogenesis could proceed past the pachytene stage but did not mature to stages capable of supporting oogenesis in most fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation